Analysis of the photosynthetic parameters, the yield and the quality of winter wheat - Csajbók, József; Kutasy, Erika; Pepó, Péter (Acta Agraria Debreceniensis, 2010)
The environmental adaptability of crop production is basically determined by the selection of biological background (plant species and varieties) suitable for the region and the site. The aim of our work is to parametrize the plant assimilation, its intensity, dynamics and the most important characteristics and the relationships to the quality in winter wheat trials. The measurements were carried out at the research site of the University of Debrecen in small parcel experiments. We measured the leaf net CO2 assimilation rate, stomatal conductance, intercellular CO2 level, the transpiration, the leaf temperature and the air temperature by the LICOR LI-6400 portable photosynthesis system in field trials on the nutrient supply. The soil of the experimental area is calciferous chernozem with favorable water regime. We have examined the photosynthetic activity, the productivity and yield stability of winter wheat varieties. We have compared the yield results, at similar agrotechnical conditions in seven cropyears. We also determined the quality parameters of the winter wheat varieties. Then we valued the yield stability of genotypes with the help of analysis of variance and linear regression equations. We have defined the connections between assimilation parameters, the yield stability and quality parameters of wheat varieties.